Karakteristik Peserta Didik, Kurikulum, Strategi, dan Evaluasi Pembelajaran PAI di Sekolah Menengah - Haditsa Qur'ani Nurhakim; Dian Wildan; Fahad Abdusomad; Bambang Samsul Arifin (Ta’dib : Jurnal Pendidikan Islam, 2025)
This study aims to comprehensively examine the characteristics of students in secondary schools, the Islamic Religious Education (PAI) curriculum implemented, learning strategies that are relevant to the developmental needs of adolescents, and effective learning evaluation within the context of Islamic education. The research employs a library research method with a descriptive-analytical approach. The findings indicate that Islamic Religious Education at the secondary school level should be oriented toward the development of students’ spiritual, moral, and social aspects through a holistic curriculum approach, active learning strategies, and authentic assessment. Character education based on Islamic values needs to be systematically integrated to realize the objectives of national education and Islamic values in a sustainable manner.